Enhancement of the starting-up enterprises using sociotransformative entrepreneurship education and its implementation using new media: a case of Malaysia - Raja Suzana Raja Kasim; Zulazli Hashim; Mokhtarrudin Ahmad (2018)
The emerging of socio-transformative entrepreneurship education concept and its achievements appear to be mostly at the policy and strategy level. In this paper, the researchers argued that the bulk of research on cross-cultural education linking entrepreneurship and new media has focused on the affective domain, and not on how culturally/socially relevant teaching, curriculum and or policies may impact the students’ learning of entrepreneurship. The impacts of research findings in the entrepreneurship education field on new media related to teacher practice, student learning and policy appear to be minimal. This is primarily due to the disconnection between cross-cultural education research and enterprise research. The primary motivation of this paper is to examine a more systemic approach by which the new media could offer in the enterprise education such as its curriculum, pedagogy and for who the specific contexts of enterprise education appears to be of relevance. Rodriguez’s (2008) theory on social justice was integrated into the idea of theory of learning; and served as a theoretical framework in this paper. Known as socio-transformative constructivism, the robustness of Rodriquez (2008) was tested among 126 entrepreneurship students in Malaysia. Using quantitative survey, data was analysed with multiple regression model. Results indicate that the context of enterprise curriculum, pedagogy, policy and understanding the mind-set of students in setting up an enterprise cannot be separated from new media presence in this knowledge era. It was further argued that students’ cultural, social, historical and academic location should be made aligned with the context of usage of new media in the aspect of teaching and learning of enterprise education. There is positive and significant relationship between new media offers in teaching and learning and the enterprise education delivery. The findings support the elements of sociotransformation entrepreneurship education concept where the students were able to use new media such as blended-learning in fueling further implementation of the teaching and learning concept. Future research should enhance the good and practical ideas while expanding the application of policies and strategies to adopt life-long learning skills for entrepreneurship students.